PENGARUH PENYALURAN KREDIT CEPAT DAN AMAN (KCA) TERHADAP PROFITABILITAS PADA PT. PEGADAIAN SYARIAH (PERSERO) CABANG HASANUDDIN KABUPATEN GOWA - NUR ALISA; AHMAD ALI; MUH. ILHAM WARDHANA HAERUDDIN (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
This study aims to determine the effect of Fast and Secure Credit Distribution (KCA) on Profitability at PT. Pegadaian Syariah (Persero) Hasanuddin Branch, Gowa Regency. The population in this study were all financial statements of PT Pegadaian Dyariah Hasanuddin Branch in 2015-2019. The sample in this study consisted of the Balance Sheet, Profit and Loss Statement and KCA Report of PT Pegadaian Syariah Hasanuddin Branch in a row 2015-2019. The data in this study is secondary data with data collection techniques using the method of observation and documentation of the company’s annual report. The data analysis technique used simple linear regression analysis. The results of this study indicate that the distribution of Fast Secured Credit (KCA) has a significant effect on profitability which is proxyed by Return On Asset, it can be seen in the significance value of 0.001 which is smaller than the 0.05 value, meaning that H1 is accepted.